Принцесса на Кириешках: [роман] / Дарья Донцова - Донцова Дарья Аркадьевна (Иронический детектив, 2004)
Экземпляры: (20141203) / Инвентарный номер: 30221 / Цена: 69.10, 70.00 / Сис.шифр: Р2 / Авт.знак: Д 67 / ГРНТИ: 17 / ББК: 84(2Рос=Рус)6